Basic Sanitation With Diarrhea - Lahming, Lahming; B, Muslimin; Indrayadi, Indrayadi; Singga, Siprianus; Yermi, Yermi; Ata Maran, Albertus; Wahyuni, Sri (International Journal of Health Sciences, 2023)
Aroppoe hamlet is the hamlet with the highest number of cases of diarrhea. The data obtained shows that the hamlet is one of the most densely populated hamlets with a total of 389 heads of household. There are many houses whose latrines do not meet health requirements, and the average clean water consumed is from dug wells, as well as air pollution. as a result of sewerage that does not meet health requirements. The purpose of this study was to determine basic environmental sanitation with the incidence of diarrhea in Aroppoe Hamlet, Tellumpanua Village, Tanete Rilau District, Barru Regency. The type of research used was an analytic survey research with a cross sectional study approach from a sample of 60 families of a total population of 289 families. Data presentation was carried out in the form of a table distribution accompanied by an explanation in the form of a narrative, and data analysis used the Chi-Square statistical test. The results showed that there was a relationship between the condition of clean water and the incidence of diarrhea (p=0.01), there was no relationship between the condition of the sewerage (SPAL) and the incidence of diarrhea (p=0.1). There is a relationship between the condition of the latrine and the incidence of diarrhea (p=0.03). There is a relationship between the state of clean water and latrines. The conclusion is that the lack of healthy toilet facilities is due to the lack of a residential environmental sanitation program targeting house floors and physical handling of clean water quality in Aroppoe Hamlet, Tellumpanua Village, Tanete Rilau District, Barru Regency.